Yo' mama is so– with nasty pubdowns of famous people by famous people : 1, 042 insults, comebacks, putdowns & wisecracks about yo' whole family! /: 1, 042 insults, comebacks, putdowns & wisecracks about yo' whole family!. (2007) - Unknown
No abstract available